Slovenski literarni prevod (1550-2000) - Stanovnik, Majda (Studia litteraria, 2005)
The following pattern is suggested by a survey of the changing position and reputation of Slovenian literary translation alongside native Slovenian literature during their coexistence from their beginnings in the mid-16th century to the end of the 20th century: